Counselling attitude as mediator between adult attachment and cybersex activities among undergraduate students in a public university in Malaysia - Hawafi, Harisa (2017)
The existence of internet has changed human behaviour in many aspects of life. The number of internet subscribers in Malaysia has been increasing tremendously. This scenario contributed to the growth of internet usage which has caused profound shifts in the way people interact and behave. There were more internet-related social problems and issue such as cybersex activities has received significant attention from people. The main objective of this research is to examine the mediating roles of counselling attitudes on the relationship between adult attachment and cybersex activities among undergraduate in a public university. This research employed descriptive and correlational research design. The respondents (n = 269) were selected through multistage random cluster sampling. Self-administered questionnaires were distributed to the respondents in the collegial residences at a public university. The data were analysed using SPSS 22.0 for descriptive analysis and AMOS 22.0 for inferential analysis. Majority of the respondents (82.50%) have medium level of counselling help-seeking attitude. While for adult attachment style, the dominant pattern of adult attachment style among respondents is adult attachment close (M= 3.223, SD= 0.539). Next, for cybersex activities, the majority of respondents (63.9%) have low level of cybersex activities. A hypothesized model was established to examine the direct and indirect effect between variables. This model was admissible (GFI= .908, AGFI= .879, CFI=.922, IFI=.924, NFI=.910, TLI=.907, RMSEA=.047). The results show there are no significant direct effect of all types adult attachment styles on cybersex activities. However, there is a significant direct effect between all adult attachment styles on negative counselling attitudes. For counselling attitudes, there is significant direct relationship between negative counselling attitudes on cybersex. The model shows that counselling attitudes is a full mediator between adult attachment and cybersex activities. This study shows the adult attachment is not directly influence university students in cybersex activities, but, they involved in cybersex activities if they have negative counselling attitudes. Practically, this study shows that counselling services is important to influence clients in cybersex involvement. Thus, counsellors have prominent roles to shift undergraduate students’ attachment to their boyfriend or girlfriend from secure attachment to insecure attachment. The prevention programs on cybersex engagement is effective if the counsellors help clients to get rid of their negative attitudes.